Perancangan UI/UX Design Aplikasi Pemesanan Sayur Berbasis Mobile Menggunakan Design Thinking - Cantika, Berliana Nala; Susetyo, Yeremia Alfa (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
One of the most common problems is how to save time without going to the market. In addition, it is difficult to search for vegetables by type, quality, price and other factors. Therefore, this application is designed to provide solutions that bring convenience and meet the needs of users. The purpose of this study is to apply the design thinking method in making UI/UX design for mobile-based vegetable ordering applications. Design Thinking is a method that focuses on innovation and consumers, in addition to paying attention to user needs and combining them with appropriate technological features so that they become good products due to their feasibility. Empathize, define, ideate, prototype, and testing are the 5 stages of the design thinking method. Next, use the System Usability Scale as a testing stage. Based on the test results on the aspect of satisfaction obtained a score of 91 with the assessment of adjective ratings is “Excellent“, while the grade scale gives the results of”A".